The employer's prerogatives and towhat extent the law has entrenched those prerogatives under the industrial relations act, 1967.can the employees challenge this matter in the industrial court?" / Noor Aza Ahmad - Ahmad, Noor Aza (Faculty of Law, 1986)
In any industrial organisations there are two parties involve, the employer and the employees, where the employer is the owner. In the old days, the relationship between the employer and employees was known as the relationship of 'master' and 'servant', which was more strict than today.